Ten Years after the Coup D'état: Rupture of a Popular National Process and Security of the Right in Honduras - Guzmán Padilla, Génesis (2019)
After 10 years, much has been written about the 2009 coup d’état in Honduras and its effects, both domestically and in relation to the regional geopolitics of Central and Latin America. However, most analysts have favored approaches that focus on institutional, political culture and state capture aspects of the conflict, while paying little attention to the Honduran history and the processes that created the conditions of possibility for the ousting of Manuel Zelaya Rosales. To go beyond these shortcomings, we propose an approach to the coup d’état that understands it as part of the process of implementation of the neoliberal project in Honduras, and the accompanying processes of state and class formation.